Synthesis of Ti/TiB Composites via Hydrogen-Assisted Blended Elemental Powder Metallurgy - Song, Yuchao; Dong, Shucheng; Stasiuk, Oleksandr; Savvakin, Dmytro; Ivasishin, Orest (Frontiers in Materials, 2020)
Titanium–titanium boride (Ti/TiB) metal matrix composites have been widely identified as promising materials for various applications. The traditional ingot metallurgy processing strategies used to fabricate these materials are energy intensive and have fallen short of their perceived mass production potentials. Powder metallurgy processing, especially that aimed at in-situ synthesis of Ti/TiB composites from titanium and TiB2 powder blends, is currently widely used for cost-efficient production of such composites. However, this approach usually results in excessive sintered porosities and associated mechanical property degradation. Therefore, further thermomechanical or hot isostatic pressing (HIP) steps are required for porosity reduction. In the present study, low-porosity Ti/TiB composites were synthesized using TiH2 and TiB2 powders via a simple press-and-sinter hydrogen-assisted blended elemental powder metallurgy route. The manufacturing route included two stages. Compaction and vacuum sintering of the noted blended powders was followed by hydrogenation and ball milling of the pre-sintered product to produce a hydrogenated, pre-alloyed powder. This was followed by compaction and final sintering. X-ray diffraction (XRD), light microscope (LM), and scanning electron microscope (SEM) were employed to investigate the powder morphology and material microstructures after various processing steps. The role of temporary alloying with hydrogen was established in tailoring the microstructure. When an optimized particle size distribution that was carefully controlled using a Malvern Mastersizer laser analyzer was combined with optimized hydrogenated pre-alloyed Ti/TiB powder compaction and sintering parameters, a nearly dense, uniform composite was formed. The above approach can be considered a promising solution for economical manufacturing of Ti/TiB parts with improved properties, i.e., with high performance-to-cost ratios.